2010
DOI: 10.1111/j.1939-1676.2010.0633.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Signs, Imaging Features, Neuropathology, and Outcome in Cats and Dogs with Central Nervous System Cryptococcosis from California

Abstract: Background: Cryptococcus spp. is a fungal pathogen with a predilection for the central nervous system (CNS). Objectives: To compare the clinical, advanced imaging, and neuropathologic findings in dogs and cats with CNS cryptococcosis, and to evaluate outcome of treatment in these animals.Animals: Twenty-six cats and 21 dogs with CNS cryptococcosis. Methods: Medical records were reviewed for clinical findings and results of CNS imaging. Archived cerebrospinal fluid and CNS tissue specimens were reviewed for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
174
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(185 citation statements)
references
References 27 publications
4
174
1
6
Order By: Relevance
“…Um trabalho que avaliou onze amostras de criptococose cerebral em gatos observou que em nove animais a inflamação era discreta (Sykes et al 2010). Isso pode ser explicado pela presença da sua cápsula, que possui propriedades que dificultam a fagocitose de macrófagos e neutrófilos e ainda interfere na migração de neutrófilos para os tecidos (Lester et al 2011).…”
Section: Discussionunclassified
“…Um trabalho que avaliou onze amostras de criptococose cerebral em gatos observou que em nove animais a inflamação era discreta (Sykes et al 2010). Isso pode ser explicado pela presença da sua cápsula, que possui propriedades que dificultam a fagocitose de macrófagos e neutrófilos e ainda interfere na migração de neutrófilos para os tecidos (Lester et al 2011).…”
Section: Discussionunclassified
“…Although infections due to C. gattii are frequent and increasing in dogs from North America [5,11,12,14,15] and Australia [16,17], there is little information relative to the occurrence of this fungus in dogs from Brazil, with only one report of C. gattii cryptococcosis [18]. Conversely, human cryptococcosis is endemic with a distinct regionalized occurrence in Brazil; cases due to C. neoformans are widespread and occur throughout the entire country, while C. gattii-associated cryptococcosis is predominant within the northeastern region, with sporadic cases occurring in Southern Brazil [8].…”
Section: Introductionmentioning
confidence: 99%
“…Eye involvement, characterized by chorioretinitis and blindness, is not uncommon. Single or multiple cryptococcomas can occur in the brain and spinal cord (181). Unlike in koalas and horses (see below), lung manifestations, including pyothorax, are uncommon (180).…”
Section: Gattii Infection In Animalsmentioning
confidence: 99%
“…These aspects are not reviewed, but the salient features of C. gattii infection in various animals are presented. Case reports and moderate-to-large case series of C. gattii in cats abound (37,169,(171)(172)(173)(176)(177)(178)(179)(180)(181)(182). A review of the major studies where the etiologic cryptococcal species were reported indicates that there are no clinical features which reliably distinguish disease caused by C. neoformans from that due to C. gattii.…”
Section: Gattii Infection In Animalsmentioning
confidence: 99%